Neighbourhood income gradients in hospitalisations due to motor vehicle traffic incidents among Canadian children. Issue 3 (3rd June 2009) - Oliver, L; Kohen, D
Abstract : Objective: To investigate income gradients in motor vehicle traffic injury hospitalisation for vehicle occupants and pedestrians/cyclists among children in urban and rural Canada. Design: Four years (2001/02–2004/05) of acute-care hospitalisation discharge records for children aged 0–19 years were analysed. International Classification of Disease codes were used to determine hospitalisations due to motor vehicle traffic incidents for occupants and pedestrians/cyclists. Rates of injury (per 10 000 person years) were calculated by neighbourhood income quintiles for urban and rural areas. Results: Among children (0–19 years), rates of vehicle occupant hospitalisation were higher in rural (5.07, 95% CI 4.90 to 5.25) than urban areas (2.08, 95% CI 2.03 to 2.14). In rural areas, children from lower income neighbourhoods had higher vehicle occupant hospitalisation rates than those from the richest neighbourhoods (5.52, 95% CI 5.13 to 5.93 vs 4.30, 95% CI 3.97 to 4.66). In urban areas vehicle occupant hospitalisation rates were similar among children from the poorest and richest neighbourhoods—but higher among children from middle income neighbourhoods. In urban areas, but not rural areas, the hospitalisation rate for pedestrians/cyclists systematically increased with decreasing neighbourhood income. In urban areas the pedestrian/cyclist hospitalisation rate was four times higher for children from the poorest (1.40, 95% CI 1.25 to 1.57) than from the richest (0.34, 95% CI 0.28 to 0.43) neighbourhoods. Conclusions: While vehicle occupant and pedestrian/cyclist motor vehicle traffic injuries are more frequent among children from lower income neighbourhoods, gradients are most pronounced for pedestrians/cyclists in urban areas.